An ontology-based approach for representing the interaction process between user profile and its context for collaborative learning environments. (October 2015) - Luna, Vladimir; Quintero, Rolando; Torres, Miguel; Moreno-Ibarra, Marco; Guzmán, Giovanni; Escamilla, Imelda
Highlights: This work is focused on defining user profiles based on ontologies. The research proposes the evolution operation that interacts with ontologies. This work defines an approach to represent the interaction process between user profiles and their context. The application of this work is oriented toward establishing adequate user profiles for recommender systems. Abstract: Recent researches about the personalized content generation have focused their efforts on two main topics: the first topic is the user model definition, i.e. the dimensions to be taken into account to represent the user, and the second topic is about the techniques used by recommender systems to provide recommendations according to the user requirements, such as adaptive approaches for context-aware systems, collaborative learning, and recommender systems for mobile environments. In this work, an approach based on ontologies to represent the interaction process between user profile and its context for collaborative learning is presented. We also analyzed the role assignments, permissions, restrictions and the definition of rules that are applied to the user, particularly in the collaborative learning context where the subject is involved. A case study related to the context of a school as well as the defined roles by the occupations in the context of locations is proposed.